(untitled) (Journal of actual problems of jurisprudence, 2019)
In the study of the problems of conflicts and social deviations in the behavior of minors, it is necessary to proceed from the General thesis that the epistemological roots of the study of problems of conflicts are interdisciplinary in nature, involving an integrated approach to their solution using the scientific achievements of many Sciences: philosophy, logic, sociology, law, pedagogy, psychology, psychiatry, etc. Among the various areas of legal sociology is becoming increasingly important legal (legal) conflictology, which studies the legal relations, norms and institutions in terms of their use for the prevention, prevention and resolution of conflicts. This problem for legal science is new for two reasons: first, due to the lack of development of General conflictology as an independent complex socio-psychological discipline; secondly, the dogmatic study of the law without studying the nature of the conflict and social deviations in the behavior of minors does not contribute to a broader understanding of it, including as a tool for dealing with social and psychological conflicts.